Investment and Capital Investment in Indonesia: PMDN, PMA, and Investment Policies - Indri Nailatul Ma'rifah; Rifqi Rifqi (Penerbit Hellow Pustaka, 2025)
Investment and capital investment are important factors in driving economic growth and national development. Investment is defined as the allocation of funds to financial and real assets with the objective of generating future returns, accompanied by a certain level of risk. Meanwhile, capital investment refers to the placement of capital, originating from both domestic and foreign sources, to undertake business activities that contribute to increased production capacity, job creation, and economic growth. This paper discusses the concepts of investment and capital investment, the types of investment based on form, source of capital, time horizon, and investor involvement, as well as the role of investment in Indonesia’s economic growth. The findings indicate that domestic investment (PMDN) and foreign direct investment (PMA) have a positive impact on the increase in Gross Regional Domestic Product (GRDP), although their effects vary across sectors and regions. Foreign direct investment has been shown to promote technology transfer and the expansion of the industrial sector, while domestic investment strengthens the local economy. Nevertheless, the implementation of investment in Indonesia continues to face several challenges, particularly related to legal uncertainty, overlapping regulations, and the effectiveness of policies at the regional level. Therefore, consistent government policies, improvements in infrastructure and human resource quality, and regulatory harmonization are required to ensure that the benefits of investment are distributed equitably and sustainably.